Pemikiran Pendidikan Islam Syed Muhammad Naquib Al-Attas dan Relevansinya dengan Problematika Pendidikan Islam Indonesia - Ahmadi Ahmadi; Muhtadi Abd. Mun'im; Riadlatul Amalia (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
This article seeks to uncover Syed Muhammad Naquib Al-Attas's thoughts on Islamic education and its relevance to the phenomenon of education in Indonesia. Where in October 2022 there were seven professors who stopped teaching, some even resigned due to pressure from their faculty leaders. This research uses a literature approach with primary sources by Syed Muhammad Naquib Al-Attas and utilizes other secondary sources. From the results of the study, it was found that Al-Attas emphasized on adab, the government's firm action on the phenomenon of education in Indonesia can be interpreted as the implementation of ta'dīb Al-Attas, making people civilized, by not dwarfing educational institutions as diploma makers.